2012
DOI: 10.1016/j.radi.2012.07.004
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between workshop and DVD methods of training for physiotherapists in diagnostic ultrasound

Abstract: The aim of this study was to evaluate the training package for improved educational outcome and to ascertain if there was a difference in outcome between two forms of delivery. The training package was delivered either during a workshop, where the training package was delivered face to face, or via a self paced DVD, which was mailed to participants. Both participant groups completed a web based assessment prior to and at the completion of the training. The assessment assessed their knowledge in ultrasound phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
3
1
Order By: Relevance
“…The results obtained in our study for the scores of the theoretical exam did not indicated very large differences between the Online 1 and Onsite 1 groups (0.6708, SE = 0.2680) but significant differences were found between the Online 2 and Onsite 2 groups (1.1832, SE = 0.5425), probably due to cumulative education time in favor of the online group. These results are in discordance with previous studies [29,31]; however, Vegas et al [31] and Krishnan et al [33] concluded that online teaching could be beneficial when associated with traditional training.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…The results obtained in our study for the scores of the theoretical exam did not indicated very large differences between the Online 1 and Onsite 1 groups (0.6708, SE = 0.2680) but significant differences were found between the Online 2 and Onsite 2 groups (1.1832, SE = 0.5425), probably due to cumulative education time in favor of the online group. These results are in discordance with previous studies [29,31]; however, Vegas et al [31] and Krishnan et al [33] concluded that online teaching could be beneficial when associated with traditional training.…”
Section: Discussioncontrasting
confidence: 94%
“…Other studies [29,31] comparing traditional teaching with online teaching showed good results for both groups but without differences between groups. Fernandez-Lao et al [27] used a mobile app for ultrasound exploration versus traditional exploration, and found no significant difference between groups in the acquisition of theoretical and practical knowledge.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, enhanced knowledge may not result in training to transfer to the clinic. 17 Other educational designs incorporate simulation training to improve confidence and contribute to the transfer of training to application. [18][19][20] For example, training programs for the Focused Assessment Sonography for Trauma, a point-of-care ultrasound examination, have successfully used simulation-based blended learning models (ie, a combination of asynchronous and synchronous learning activities) to enhance learning experiences.…”
Section: Introductionmentioning
confidence: 99%